2005
DOI: 10.1200/jco.2005.03.156
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Resistance and Incomplete Response to Docetaxel by Gene Expression Profiling in Breast Cancer Patients

Abstract: A specific and consistent gene expression pattern was found in residual tumors after docetaxel treatment. These profiles provide therapeutic targets that could lead to improved treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 20 publications
5
104
0
3
Order By: Relevance
“…One explanation for these findings is that breast tumors comprise a population of chemoresistant TIC. Indeed recent studies of patient tumors before and after therapy support the contention that breast TIC are chemo-resistant and underscore the need to develop therapies that target these cells (Chang et al, 2005;Li et al, 2008;Creighton et al, 2009). Our findings illustrate that MRK-003 targets breast TIC as well as non-tumorigenic tumor cells without any deleterious consequences for adult stem cells and thus provides proof-of-principle that eliminating these cells can afford long-lasting cancer cures.…”
Section: Mrk-003 Shrinks and Eliminates Tumors In Micesupporting
confidence: 58%
“…One explanation for these findings is that breast tumors comprise a population of chemoresistant TIC. Indeed recent studies of patient tumors before and after therapy support the contention that breast TIC are chemo-resistant and underscore the need to develop therapies that target these cells (Chang et al, 2005;Li et al, 2008;Creighton et al, 2009). Our findings illustrate that MRK-003 targets breast TIC as well as non-tumorigenic tumor cells without any deleterious consequences for adult stem cells and thus provides proof-of-principle that eliminating these cells can afford long-lasting cancer cures.…”
Section: Mrk-003 Shrinks and Eliminates Tumors In Micesupporting
confidence: 58%
“…This result is therefore in agreement with the Nomograms's design proposed online, which does not take into account the histological type of the tumour when deciding on the therapeutic option (Rouzier et al, 2005b). There is room to better define biological predictive factors of response to neoadjuvant chemotherapy to screen patients who would benefit most from this therapeutic option (Sotiriou et al, 2002;Chang et al, 2005;Gianni et al, 2005;Rouzier et al, 2005a;Pierga et al, 2007). Lobular carcinomas had reduced clinical responses to neoadjuvant chemotherapy, while responses to breast-conserving treatments were fewer, although not significantly (54% (42 out of 78) vs 65% (434 out of 672); P ¼ 0.07).…”
Section: Discussionsupporting
confidence: 79%
“…This was demonstrated for chemotherapy by Hannemann et al (2005), who observed that tumours that responded to neoadjuvant chemotherapy showed dramatic changes in their expression profiles when compared to the changes observed in non-responders (Hannemann et al, 2005). On the other hand, a comparison between the transcriptomic profiles of tumours subjected to taxane-based neoadjuvant chemotherapy before and 3 months after treatment revealed strikingly different patterns, independent of initial sensitivity or resistance (Chang et al, 2005b). Cell line studies have demonstrated that changes in gene copy numbers may lead to acquired resistance to chemotherapy (Leyland-Jones et al, 1999;Shimizu et al, 2002;Yasui et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Gene 'signatures' or predictors have been devised for several chemotherapy regimens, including paclitaxel followed by fluorouracil, AC, AC/doxorubicindocetaxel and taxane only chemotherapy (Chang et al, 2003(Chang et al, , 2005bAyers et al, 2004;Hannemann et al, 2005;Cleator et al, 2006). Although these results are promising, the exceedingly small sample size and limitations with the current technology and analysis methods have so far precluded definitive conclusions (Brenton et al, 2005;Reis-Filho et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%